The Effect of Single Bout of Acute Exercise on Working Memory Performance - Deo, Santosh Kumar; Agrawal, Kopila; Bhattrai, Prem; Chaudhary, Raju Kumar (Birat Journal of Health Sciences, 2018)
Introduction: Working memory is a kind of short term memory important for reasoning and guiding decision-making and behavioral process. Objective: The goal of the present research was to study the outcome of single bout of acute moderate-intensity exercise on working memory. Methodology: Twenty two male subjects were asked to perform working memory task by 2n back task in baseline resting, immediately after exercise and after five minute of exercise session. 3 minute step test procedure was used as a moderate intensity exercise intervention. Results: The percentage correctness of 2n back task of working memory was found to be 64.36% for baseline resting condition, 78.01 % for immediately after 3-minute step test and 80.70% for 5 minute after the exercise. In both exercise session (i.e. immediately after exercise and after 5 minute of exercise), significant improvement (p value <0.05) in working memory was seen as compared to the baseline resting session while no such significant beneficial improvement was seen when compared between immediately after exercise and after 5 minute of exercise. Conclusion: Improvement in working memory after moderate exercise intervention was seen, which is important for learning and memory and decision-making. BJHS 2018;3(2)6:484-487.